Optymalizacja tras dostarczania prasy w sieci dystrybucji bezpośredniej - Hanczar, Paweł (Routes Optimalization for Direct Distribution Networks, 2005)
The article presents application of vehicle routing models for optimizing direct distribution networks. Wroclaw advertisement paper distribution network was used as the research base. In the first part of the article the current solution was presented. The second part contains the presentation of new routing set. The conclusion contains the comparison of presented solutions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 224-231